Human semen quality and environmental and occupational exposure to pollutants: A systematic review - Cofone, L.; Pindinello, I.; D'Ancona, G.; Grassi, F.; Antonucci, A.; Vitali, M.; Protano, C. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The aim of the present systematic review was to evaluate the correlation between the exposure to environmental and/or occupational pollutants and possible alteration of semen quality, focalizing the attention on the studies performed using a biomonitoring approach. Methods. The review was conducted from inception to May 11 2023, according to the PRISMA Statement 2020 and using the following databases: Scopus, Pubmed and Web of Science. The protocol was registered on PROSPERO (CRD42023405607). Studies were considered eligible if they reported data about the association between exposure to environmental pollutants and alteration of semen quality using human biomonitoring. The quality assessment was carried out by the use of the Newcastle-Ottawa Quality Assessment Scale. Results. In total, 21 articles were included, conducted in several countries. The main matrices used for biomonitoring were urine and blood and the most sought-after contaminants were bisphenols, phthalates, pesticides, polychlorinated biphenyls, polycyclic aromatic hydrocarbons, heavy metals and other inorganic trace elements. The results of the studies demonstrated a significant positive correlation between the increase of the pollutants’ levels in the biological matrices examined and some alterations of the semen quality indicators, such as a decrease in motility, concentration and morphology of the spermatozoa. Conclusions. Male fertility can be negatively affected by the exposure to environmental and/or occupational pollutants. Human biomonitoring programs may be considered a useful tool for specific surveillance programs devoted to early highlight subjects who are more exposed to environmental pollutants in order to reduce risk exposure.